Interannual changes of austral summer coccolithophore assemblages and southward expanse in the Southern Indian Ocean. (August 2020) - Patil, Shramik M.; Mohan, Rahul; Shetye, Suhas S.; Gazi, Sahina; Choudhari, Pallavi; Jafar, Syed
Abstract: Coccolithophore ecology and biogeography in the Southern Indian Ocean was studied during the austral summer of 2009 (SOE09; late austral summer), 2010 (SOE10; mid-austral summer), and 2012 (ISEA12; early austral summer). During the SOE09 and SOE10, surface water samples (55 and 54 water samples, respectively) were collected from two different transects between Mauritius and Antarctica (~48°E; ~57.3°E); whereas during the ISEA12, 22 sea surface water samples were collected between Cape-Town and Prydz Bay. Highest coccolithophore diversity was during SOE10 (36 taxa), followed by SOE09 and ISEA12 (12 and 7 taxa, respectively) whereas, highest coccolithophore abundance was reported during the ISEA12 (up to 2203 × 10 3 coccospheres/l) followed by SOE10 (up to 742 × 10 3 coccospheres/l) and SOE09 (up to 217 × 10 3 coccospheres/l). During each expedition, elevated coccolithophore diversity was documented at the Subtropical zone whereas the highest abundance was recorded at the Subantarctic zone, which was dominated by Emiliania huxleyi . Differences in the occurrence and southward expanse of coccolithophores were documented during each expedition, i.e. maximum southward expanse during the SOE10 and lowest during the ISEA12. We show that, biogeographic boundaries of coccolithophores are highly variable in the Southern Indian Ocean which is controlled by environmental factors in the early and mid-austral summer, and grazing pressure in the late austral summer. In addition, the physical forcing also may play a key role in transport of coccoliths and coccospheres in the high latitudes. We indicate that, southward expanse of coccolithophores is significant and may occur for short periods during austral summer.